HUBUNGAN ANTARA KONSEP DIRI AKADEMIK DAN KERAGUAN MENGAMBIL KEPUTUSAN KARIR DENGAN KEMATANGAN KARIR PADA SISWA KELAS XII SMK NEGERI 3 KOTA SALATIGA - Hana Septa Linda (Program Studi S1 Psikologi, 2017)
This study aims to know the relationship between the academic self concept and career decision making difficulties with career maturity of class XII at SMK Negeri 3 Kota Salatiga. Sampling using purposive sampling technique with term participants as many as 204 respondents. Measuring instruments used in the study is a modification of Career Maturity Inventory (CMI) – Form C which is composed by Crites & Savickas (2011), Academic Self-Concept Questionnaire developed by Liu, Wang & Parkins (2005), and Career Decision Making Difficulties Questionnaire CDDQ (Gati, Krausz & Osipow, 1996). Data analysis techniques used Ordinal Regression or Ordinal Analysis. The results indicated by chi-square value amounted to 58,353 (>7,815) or change -2Log Likelihood from 94,855 become 36,502 and significantly 0,000 (<0,05), which means the academic self concept and career decision making difficulties take simultaneous significantly with career maturity of class XII at SMK Negeri 3 Kota Salatiga with 29.1% contribution based on Cox and Snell's analysis.